Las audiencias de las retransmisiones y programas de deportes de Televisión de Galicia desde 1990 hasta 1996 - Varela Rodríguez, Aurora Peregrina (1998)
"The doctoral thesis "The tv sharings of the live sports broadcasts and sports programmes in TV Galicia since 1990 untill 1996", studies the number of viewers that have followed the sports programming of this regional tv network during those six years. The aim was to analyse the technology that this network has dedicated to produce the football live broadcasts and also to study the laws that affected these sort of tv broadcasts. In this investigation there is evidence that the football live broadcasts achieved great shares with some of the key football matches, exceeding the shares reached by the other programmes broadcasted by the same network. The report studies also the profiles of the viewers of those programmes with better shares, and investigates until which point the expenses made by TVG to acquire the rights and to produce these football programmes meet any revenues. The reference of this thesis has been Television of Galicia, because among the other five regional televisions that belong to FORTA, is one of those who has the exclusive right to broadcast the first and second division matches and the King Football Cup (except the final match), according to the agreement signed on the 06th of July 1990 by The National League of professional football and the regional tv stations. At the end of this report you can find the results obtained by the investigation ."